1988
DOI: 10.1164/ajrccm/137.6.1285
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nasal Flow on Breathlessness in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Many patients with chronic obstructive pulmonary disease (COPD) receiving supplemental oxygen state that this treatment makes them less short of breath at rest. We postulated that this phenomenon may be related to improved arterial oxygenation, reduced ventilation, or stimulation of nasal receptors caused by the flow of gas. Eight patients who reported this phenomenon were studied in a quiet room. Each patient received zero flow, 2, or 4 L/min of air or oxygen through nasal cannula for 5 min at each level in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 7 publications
0
43
0
3
Order By: Relevance
“…Oxygen via nasal prongs was included in the study protocol, as there is a theoretical potential for inhaled morphine to lower oxygen saturation. Although the effect of supplemental oxygen on dyspnoea at rest has been disputed [18], at least two studies have shown that oxygen reduces dyspnoea at rest to a greater extent than air (delivered in similar fashion) in hypoxaemic patients with COPD [19], or with terminal cancer [20]. In the present study, the beneficial effect on dyspnoea cannot be ascribed to oxygen, since an equal efficacy was obtained with 10 mg nebulized morphine, without the addition of oxygen.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Oxygen via nasal prongs was included in the study protocol, as there is a theoretical potential for inhaled morphine to lower oxygen saturation. Although the effect of supplemental oxygen on dyspnoea at rest has been disputed [18], at least two studies have shown that oxygen reduces dyspnoea at rest to a greater extent than air (delivered in similar fashion) in hypoxaemic patients with COPD [19], or with terminal cancer [20]. In the present study, the beneficial effect on dyspnoea cannot be ascribed to oxygen, since an equal efficacy was obtained with 10 mg nebulized morphine, without the addition of oxygen.…”
Section: Discussionmentioning
confidence: 49%
“…A placebo effect of similar magnitude on dyspnoea at rest has been demonstrated previously following nebulized saline in patients with severe asthma or COPD [7]. Other studies have provided arguments in favour of a nonspecific reduction in dyspnoea related to the use of either nasal prongs [18], or a face mask [21].…”
Section: Discussionmentioning
confidence: 53%
“…It is possible that oxygen delivered to hypoxic subjects after exercise may reduce dyspnoea via similar mechanisms to those described during exercise and indeed oxygen delivered after exercise has recently been reported to reduce dynamic hyperinflation [8]. A further study comparing oxygen with air given to hypoxic subjects at rest, demonstrated no difference in dyspnoea but all subjects were significantly more dyspnoeic during administration of both gases when topical anaesthesia had been applied to the nasal passages [24]. This suggests a role for nonspecific stimulation of nasal receptors by gas flow in the modulation of dyspnoea and could explain why oxygen did not reduce dyspnoea more than air in this study.…”
Section: Discussionmentioning
confidence: 98%
“…Airflow and cooling from the fan have been postulated to influence afferent sources for respiratory sensation by stimulating upper airway "flow" receptors or trigeminal skin receptors [5,13,34,35]. The first of these mechanisms would require cooling of nasal or airway mucosa, whereas the second could be achieved by cooling the facial skin.…”
Section: Discussionmentioning
confidence: 99%